Exploring the mineral content, nutritional, and phytochemical composition of aqueous shoot extracts of bamboo for ethnopharmacological significance from the Niyamgiri hill range, Kalahandi, Odisha, India - Biswajeet Acharya; Amulyaratna Behera; Prafulla Kumar Sahu; Durga Prasad Mishra; Sukumar Purohit; Bimalendu Chowdhury; Suchismeeta Behera (Advances in Bamboo Science)
Bamboo is highly regarded for its rich nutritional value and versatility as a sustainable resource. Its unique nutraceutical properties contribute to various pharmacological effects, making it a standout in natural health and wellness. This study compared elemental, nutritional, and phytochemical characteristics of ten bamboo species (Bambusa balcooa, Bambusa bambos, Bambusa spinosa, Bambusa vulgaris, Bambusa textilis, Dendrocalamus strictus, Dendrocalamus hamiltonii, Dendrocalamus giganteus, Thyrsostachys siamensis and Fargesia nitida) collected from the Niyamgiri Hill Range in Western Odisha, India. We conducted a systematic ethnobotanical survey to collect the selected bamboo samples from the study region. Nutritional, phytochemical and elemental analyses were performed to evaluate mineral content, macronutrients, micronutrients and phytochemical composition in aqueous extract of bamboo shoots of different species. Bambusa vulgaris emerged as the most ethnopharmacologically significant bamboo species, exhibiting a cultural index of 0.96. It displayed higher levels of key nutritional and phytochemical components, including crude fibre, crude protein, neutral detergent fibre, acid detergent fibre, alkaloid, flavonoid, saponin and total energy, than the other species. Additionally, Bambusa vulgaris contained substantial quantities of essential minerals, such as potassium, phosphorus, iron, copper, calcium and magnesium. These findings offer valuable insights into the diversity of these bamboo species and their potential applications in nutrition and industry. The composition and quantitative determination of specific compounds provide useful insights that could reveal their potential uses and aid in developing new drugs and formulations, contributing to sustainable resource utilization.